Fausse extase et vrai fou : l'artifice revendiqué dans quelques poèmes de John Donne - Guillaume Fourcade (Sillages Critiques)
Because it flaunts its deceptiveness, any artificial object always simultaneously denounces it. By asserting itself as a fake, it comments upon itself in a self-reflexive way and betrays as well as cancels out the trick it intended to perform. Such a shift from deceit to confession can be traced in at least three of Donne’s love poems: “The Ecstasy”, “The Triple Fool” and “The Canonization”. This article studies how, through self-referential remarks, these poems call into question their intended purpose: enfolding as consistent and unified discourse on love or containing it in a generically stable literary form. By self-consciously sapping their quest for unity and by substituting instead the fragmentation of meaning and genre, these texts stage themselves as lies and thus point out their artificial quality.